AB0717 Inflammatory Bowel Disease Associated Arthropathy: Characteristics of the Disease and Validity of Diagnoses Based on Icd-Coding in Sweden - Drivelegka, P.; Papachrysos, N.; Petersson, I.F.; Bremander, A.; Jacobsson, L.T. (Annals of the rheumatic diseases, 2014)
Background Epidemiological studies of IBD-associated arthritis (IBD-aA) are scarce, but both axial and peripheral muskuloskeletal manifestations are considered to be more common in IBD-aA than in the general population. Objectives To determine: 1) the validity of ICD-10 codes for IBD-aA in administrative databases, 2) the frequency and characteristics of axial and peripheral arthritis by type of IBD. Methods The SpA Scania cohort consists of all the subjects aged 15 years or older in the Skåne region (1.2 million inhabitants in southern Sweden) having recieved a diagnosis of any type of Spondyloarthritis during 2003-2007 at primary or specialised care visits (N=5771) recorded in the Skåne Health Care Register (SHCR). This included patients with Ankylosing Spondylitis (26%), Undiffentiated Spondyloarthritis (22%), Psoriatic Arthritis (39%) and IBD-aA (ICD-codes: M07.4, M07.5, 2.3%). Medical records were reviewed following a stuctured protocol in the subgroup of IBD-aA patients (N=65) that also responded to a postal survey sent to the Spa Scania cohort in 2009. Results Of the 65 patients with IBD-aA diagnosis in the register, 80% (n=52) and 94% had both IBD and arthritis according to the medical records when requiring ≥1 or ≥2 visits with diagnoses of IBD-aA respectively. Of the 52 patients (80%) where IBD and rheumatic disease could be verified (17 men), the mean age at the time of onset of arthritis symptoms was 39.8 years (SD: 13.9). Of the 29 patients with ulcerative colitis (UC) 83% had peripheral and 45% had axial arthritis. For Crohn's disease (CD) (n=23) the corresponding figures were 91% and 48%. In 78% of the patients, bowel disease preceded the arthritis symptoms. Only in 8 patients (15,4%) the onset of arthritis preceded the IBD and 7 of them had axial arthropathy. Overlap between peripheral and axial arthritis was found in 18 patients (34,6%). In women peripheral arthritis was more common than axial (91% vs 40%), whereas in men a more equal distribution was observed (76% vs 65%). Conclusions The ICD10 codes for IBD-aA had a high validity supporting larger epidemiological studies. Peripheral arthritis was more common than axial disease in both UC and CD. Disclosure of Interest None declared DOI 10.1136/annrheumdis-2014-eular.4540